Estudos citogenéticos em Dorstenia L. (Moraceae) - Barreto, Lucas Mesquita (2016)
Previous cytogenetic studies in Dorstenia mention that the species may have 24 to 72 chromosomes, and suggested a conserved chromosome number 2n = 32 for the Neotropic species. However, some information reported in the literature are dubious or insufficient to assess the potential of cytogenetic data to the better understand of systematics and evolution issues within this genus. Here, eight species of Neotropical Dorstenia had their karyotypes characterized, and the nuclear DNA content measured. Dorstenia bahiensis, D. cayapia, D. grazielae, D. hirta and D. turnerifolia had their karyotypes characterized and the DNA nuclear content measured for the first time. Morphological plant characters and morphometric data were submitted to cluster analysis, followed by a test of group sharpness, and ordination analysis, aiming to support the discussion about the potential of cytogenetic data to infrageneric systematic of Dorstenia. The species showed chromosome number of 2n = 32, varying in chromosomes morphology. The karyotypes least asymmetric were observed in Dorstenia elata, and the more asymmetric were registered in D. bahiensis and D. bonijesu. The 2C value ranged from 3.21 picograms (pg) D. bahiensis to 5.47 pg in D. arifolia. Morphologically similar species, like D. hirta and D. turnerifolia, grouped together based on morphometric data. The sharp groups based on morphometric data correspond to species circumscribed under the sections Dorstenia, Lecania and Emygodia, previously established based on the plant morphology. Our results supports that the chromosome number 2n = 32 is possible conserved in the Neotropical species of Dorstenia, and indicate the potential of cytogenetic data to the systematics of this genus.